Melatonin enhances the recovery of cryopreserved shoot tips of American elm (Ulmus americana L.). Issue 4 (30th September 2013) - Uchendu, Esther E.; Shukla, Mukund R.; Reed, Barbara M.; Saxena, Praveen K.
Abstract Climate change and global migrations of people and goods have exposed trees to new diseases and abiotic challenges that threaten the survival of species. In vitro germplasm storage via cryopreservation is an effective tool to ensure conservation of tree species, but plant cells and tissues are exposed to multiple stresses during the cryopreservation process. The current study was designed to evaluate the potential of melatonin to improve survival through the process of cryopreservation. Shoot tips of in vitro‐grown plantlets and dormant winter buds of American elm were successfully cryopreserved in liquid nitrogen (LN) at −196°C under controlled environmental conditions following melatonin treatment and cold acclimation with either vitrification or encapsulation–vitrification protocols. Explants had optimal regrowth following cryopreservation when treated with the plant vitrification solution#2 (PVS2) for 10 min. Supplementation of both preculture and regrowth media with melatonin significantly enhanced regrowth of frozen shoots compared with the untreated control (P < 0.05). Approximately 80–100% of shoot explants grew under optimized conditions using melatonin‐enriched media. Shoot tips of dormant winter buds consistently produced nearly 100% regrowth with both techniques. The main steps of the optimized protocol are 14‐day cold‐acclimated cultures exposed to preculture medium with 0.1–0.5 μm melatonin for 24 hr, application of PVS2 for 10 min, rapid cooling in LN, rapid rewarming, removal of cryoprotectants, and recovery on a medium supplemented with 0.1–0.5 μm melatonin. Our results demonstrate the usefulness of the antioxidant melatonin for long‐term storage of naturally resistant elm germplasm.